2016
DOI: 10.3109/02813432.2016.1160632
|View full text |Cite
|
Sign up to set email alerts
|

Norwegian general practitioners' knowledge and beliefs about breastfeeding, and their self-rated ability as breastfeeding counsellor

Abstract: BackgroundBreastfeeding is considered the best infant-feeding method. Norway is one of the leading countries in terms of breastfeeding initiation and duration. To maintain this high breastfeeding rate, it is important to understand the factors that influence breastfeeding. A doctor s advice can improve the rates of breastfeeding initiation and duration, but not all doctors are competent in breastfeeding counselling.ObjectivesThe aim of this study was to identify the knowledge and beliefs of general practitione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The lack of formal structured training, self-efficacy in accessing informal training and resource materials influenced PCPs’ mastery of postpartum care. In developed countries such as Canada [ 20 ], Norway [ 21 ] and Australia [ 22 ], PCPs similarly reported that they were aware of the benefits of breastfeeding but lacked basic knowledge to assess and advise on breastfeeding. Postpartum care training, including assessing breastfeeding and normal feeding behaviour of the baby can be incorporated into the national Family Medicine training programmes to increase the competency of PCPs in this field [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of formal structured training, self-efficacy in accessing informal training and resource materials influenced PCPs’ mastery of postpartum care. In developed countries such as Canada [ 20 ], Norway [ 21 ] and Australia [ 22 ], PCPs similarly reported that they were aware of the benefits of breastfeeding but lacked basic knowledge to assess and advise on breastfeeding. Postpartum care training, including assessing breastfeeding and normal feeding behaviour of the baby can be incorporated into the national Family Medicine training programmes to increase the competency of PCPs in this field [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These are very encouraging results. However, some studies show that physicians often misunderstand the nutritional guidelines, thus it is worth clarifying and discussing these guidelines, for example, during training meetings and workshops [22][23][24]. As a matter of fact, knowledge on the influence of nutrition during the first years of life on later health has grown significantly in recent years, both among doctors and the general population [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…A survey from the 1970s suggesting half of paediatricians and obstetricians would have benefited from a specific breastfeeding curriculum whilst at medical school [30]. This view is still relevant today with 85% Norwegian GPs believing that infant feeding should be taught before gaining their registration [12]. Additionally, doctors who reported lower confidence in breastfeeding clinical skills were less likely to engage with further training, suggesting the need to incorporate breastfeeding into a core curriculum [13].…”
Section: Improving Breastfeeding Educationmentioning
confidence: 99%
“…There are several examples in the literature of where poor knowledge and training around infant feeding has been shown to have negative impacts. In a Norwegian survey of GPs, only 26% could identify the differences between infant formula and human milk, which consequently affected their confidence in counselling patients [12]. Furthermore, approximately half of GPs and paediatricians surveyed in the UK advised parents to introduce solids before the WHO/UNICEF recommendation of around 6 months [13].…”
Section: Introductionmentioning
confidence: 99%